Structural Efficiency of Concrete Containing Crushed Bone Aggregates - Akinyele, J. O.; Kehinde, H. A.; Igba, U. T. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2020)
The indiscriminate dumping of animal waste, especially cow bones in abattoir has brought about the need for adequate safe disposal and recycling of such waste. This study investigated the use of crushed bones as a partial substitute for fine aggregate and its efficiency in concrete structures. Sieve analysis test was conducted on the crushed bone and used as partial replacement of fine aggregate in concrete at 0, 25, 50, 75, and 100% by weight.  Slump test on the fresh concrete was investigated, while the density, compressive strength test and structural efficiency of the hardened concrete were also determined. The sieve analysis result revealed that the crushed bone was poorly graded, and the slump test showed that the 25% of crushed bone concrete has a low slump. The density was 2370 kg/m3, the compressive strength was 17.10N/mm2 at 28 days, while the structural efficiency was 7.22. The 50, 75 and 100% samples has compressive strength of 16 N/mm2, 6.10N/mm2 and 4 N/mm2 at 28 days respectively and these values are far below expectations. The work concluded that crushed bones could partially replace fine aggregate in lightweight concrete at not more than 25% by weight. This test is limited to a short-term test of 28 days.